Taxonomy and phylogeny of endophytic Chaetomium (Chaetomiaceae) associated with mango ( Mangifera indica ) in Yunnan, China - Er-Fu Yang; Samantha C. Karunarathna; Abdallah M. Elgorban; Kasem Soytong; Itthayakorn Promputtha; Saowaluck Tibpromma (New Zealand Journal of Botany, 2024)
Endophytic fungi reside within plant tissues throughout their entire or partial life cycle, establishing a mutually beneficial symbiotic relationship with their host plant, free from causing any adverse effects or diseases. In addition, endophytic fungi are known as a rich source of new and physiologically active natural chemicals with great therapeutic potentials. Endophytic fungi can promote their host's growth and improve tolerance towards biotic and abiotic stresses. The endophytic fungi associated with mangoes have been infrequently studied, and most isolates lack both morphological characteristics and phylogenetic analyses. When investigating fungal endophytes associated with mango, we isolated four species of Chaetomium from fresh mango leaves, which were collected from mango trees under commercial cultivation in Honghe Prefecture, Yunnan Province, China. Based on morphological comparisons and the results of phylogenetic analyses of concatenated LSU, ITS, rpb2, and tub2 sequence data, here we introduce a new species: Chaetomium hongheensis (KUNCC22-10764, 22-10750); and two new host records: C. cochliodes (KUNCC22-10741) and C. globosum (KUNCC22-10752) from mango leaves. The two new host records were frequently reported on various substrates in China previously. In addition, the new host and country record Chaetomium unguicola (KUNCC22-10758) is first reported in this study as a mango endophyte in China.
Keywords: Plant Pathogens and Fungal Diseases; Plant Parasitism and Resistance; Mycorrhizal Fungi and Plant Interactions